Cytotoxicity and Genotoxicity Evaluation of Organochalcogens in Human Leucocytes: A Comparative Study between Ebselen, Diphenyl Diselenide, and Diphenyl Ditelluride. (21st November 2013) - Caeran Bueno, Diones; Meinerz, Daiane Francine; Allebrandt, Josiane; Waczuk, Emily Pansera; dos Santos, Danúbia Bonfanti; Mariano, Douglas Oscar Ceolin; Rocha, João Batista Teixeira
Abstract : Organochalcogens, particularly ebselen, have been used in experimental and clinical trials with borderline efficacy. (PhSe)2 and (PhTe)2 are the simplest of the diaryl dichalcogenides and share with ebselen pharmacological properties. In view of the concerns with the use of mammals in studies and the great number of new organochalcogens with potential pharmacological properties that have been synthesized, it becomes important to develop screening protocols to select compounds that are worth to be tested in vivo . This study investigated the possible use of isolated human white cells as a preliminary model to test organochalcogen toxicity. Human leucocytes were exposed to 5–50  μ M of ebselen, (PhSe)2, or (PhTe)2 . All compounds were cytotoxic (Trypan's Blue exclusion) at the highest concentration tested, and Ebselen was the most toxic. Ebselen and (PhSe)2 were genotoxic (Comet Assay) only at 50  μ M, and (PhTe)2 at 5–50  μ M. Here, the acute cytotoxicity did not correspond with in vivo toxicity of the compounds. But the genotoxicity was in the same order of the in vivo toxicity to mice. These results indicate that in vitro genotoxicity in white blood cells should be considered as an early step in the investigation of potential toxicity of organochalcogens.